Effects of substrate modifications on the arginine dimethylation activities of PRMT1 and PRMT5. Issue 1 (2nd January 2022) - Fulton, Melody D.; Dang, Tran; Brown, Tyler; Zheng, Y. George
ABSTRACT: Histone arginine methylation is a prevalent posttranslational modification (PTM) in eukaryotic cells and contributes to the histone codes for epigenetic regulation of gene transcription. In this study, we determined how local changes on adjacent residues in the histone H4 substrate regulate arginine asymmetric dimethylation and symmetric dimethylation catalysed by the major protein arginine methyltransferase (PRMT) enzymes PRMT1 and PRMT5, respectively. We found that phosphorylation at histone H4 Ser-1 site (H4S1) was inhibitory to activities of PRMT1 and PRMT5 in both monomethylating and dimethylating H4R3. Also, a positively charged H4K5 was important for PRMT1 catalysis because acetylation of H4K5 or the loss of the H4K5 ε-amine had a similar effect in reducing the catalytic efficiency of asymmetric dimethylation of H4R3. An opposite effect was observed in that acetylation of H4K5 or the loss of the H4K5 ε-amine enhanced PRMT5-mediated symmetric dimethylation of H4R3. Furthermore, we observed that N-terminal acetylation of H4 modestly decreased asymmetric dimethylation of H4R3 by PRMT1 and symmetric dimethylation of H4R3 by PRMT5. This work highlights the significance of local chemical changes in the substrate to regulating PRMT activity and unravels the pattern complexities and subtleties of histone codes.